First Report of CC5-MRSA-IV-SCCfus “Maltese Clone” in Bat Guano - Assia Mairi (MDPI AG, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) is a widespread pathogen that could cause different illnesses in both human and animals. Presence of MRSA in animals raises concerns of their capacity to act as reservoirs, particularly in wild animals. This study aimed to characterize the resistance and virulence patterns of S. aureus strains isolated from bat guano in Algeria. From March to May 2016, 98 bat guano samples from Aokas’s cave (Bejaia, Algeria) were collected. Swabs were taken for microbiological studies. Isolates were identified by Vitek® MS system, and antibiotic susceptibility was determined by disk diffusion method. The clonal origin, virulence and antibiotic resistance profiles of S. aureus isolates were characterized by whole genome sequencing. Eleven S. aureus strains were obtained from the 98 guano samples. Seven isolates were sensitive to all antibiotics tested and four (36.3%) were resistant to penicillin G, cefoxitin and fusidic acid. The four MRSA isolates were assigned to the sequence type ST149 and related to spa type t010. These isolates harbored a SCCmecIV element and the fusidic acid resistance element Q6GD50 (fusC). They carried different virulence genes including several enterotoxins (sea, egc enterotoxin locus, sec, sel), and the toxic shock syndrome toxin (tst). Our results highlight that bat guano may constitute an important reservoir of MRSA strains.